2014
DOI: 10.1111/jopr.12140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ceramic Thickness and Shade on Mechanical Properties of a Resin Luting Agent

Abstract: Variolink II irradiated through ceramic with the lowest chroma exhibited the highest elastic modulus; therefore, the light activation method might not be the same for all clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 33 publications
2
22
1
1
Order By: Relevance
“…A number of studies evaluated the degree of underlying resin cement polymerization at various ceramic thicknesses and reported conflicting results. Moraes et al 24 detected no significant differences in DC of dual-cured resin cements in 0.7, 1.4, and 2.0 mm thick ceramics, and Passos et al 32 also reported no significant differences in hardness between 1.0 and 3.0 mm thick ceramic. By contrast, Bansal et al 33 reported a significant decrease in DC of resin cement in 4 mm thick leucite-reinforced ceramic or IPS e.max Press compared with 2 or 3 mm plates.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies evaluated the degree of underlying resin cement polymerization at various ceramic thicknesses and reported conflicting results. Moraes et al 24 detected no significant differences in DC of dual-cured resin cements in 0.7, 1.4, and 2.0 mm thick ceramics, and Passos et al 32 also reported no significant differences in hardness between 1.0 and 3.0 mm thick ceramic. By contrast, Bansal et al 33 reported a significant decrease in DC of resin cement in 4 mm thick leucite-reinforced ceramic or IPS e.max Press compared with 2 or 3 mm plates.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the translucency, it has been reported that the higher the opacity, as well as the higher saturation, the lowest transmission of light source to cementing agent, which results in lower physicochemical properties ( 3 , 13 - 15 ). As observed in this research, the opaquer lithium disilicate ceramics showed lower DC during cementation compared to more translucent ceramic.…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize this problem, amine free resin cements have been recently introduced in market to promote the esthetic longevity of indirect restorations ( 13 , 14 ). Flowable composite can also be used ( 8 ), but these systems have physical activation only, and it is estimated that the light irradiance emitted by light curing unit that reaches the cement is reduced when it passes through the ceramic, reducing the degree of conversion (DC) and consequently the mechanical properties of material, which may affect the durability of indirect restorations ( 6 , 11 , 13 , 15 , 16 ). This event is dependent on light intensity, curing unit, ceramic thickness, opacity, among others ( 5 , 9 , 13 , 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic material characteristics can affect the light transmitting and resin cement's polymerization (27). Inadequate polymerization can modify physical and mechanical properties of the resin cement (28). No ceramic material was used in this study.…”
Section: Study Limitationsmentioning
confidence: 99%